Preeclampsia and cardiovascular disease share genetic risk factors on chromosome 2q22 - Løset, M.; Johnson, M.; Melton, P.; Ang, W.; Huang, R.; Mori, T.; Beilin, L.; Pennell, C.; Roten, L.; Iversen, A.; Austgulen, R.; East, C.; et al. (2014)
Objective: Four putative single nucleotide polymorphism (SNP) risk variants at the preeclampsia susceptibility locus on chromosome 2q22; rs2322659 (LCT), rs35821928 (LRP1B), rs115015150 (RND3) and rs17783344 (GCA), were recently shown to associate with known cardiovascular risk factors in a Mexican American cohort. This study aimed to further evaluate the pleiotropic effects of these preeclampsia risk variants in an independent Australian population-based cohort. Methods: The four SNPs were genotyped in the Western Australian Pregnancy Cohort (Raine) Study that included DNA, clinical and biochemical data from 1246 mothers and 1404 of their now adolescent offspring. Genotype association analyses were undertaken using the SOLAR software. Results: Nominal associations (P < 0.05) with cardiovascular risk factors were detected for all four SNPs. The LCT SNP was associated with decreased maternal height (P = 0.005) and decreased blood glucose levels in adolescents (P = 0.022). The LRP1B SNP was associated with increased maternal height (P = 0.026) and decreased maternal weight (P = 0.044). The RND3 SNP was associated with decreased triglycerides in adolescents (P = 0.001). The GCA SNP was associated with lower risk in adolescents to be born of a preeclamptic pregnancy (P = 0.003) and having a mother with prior preeclamptic pregnancy (P = 0.033). Conclusions: Our collective findings support the hypothesis that genetic mechanisms for preeclampsia and CVD are, at least in part, shared, but need to be interpreted with some caution as a Bonferroni correction for multiple testing adjusted the statistical significance threshold (adjusted P < 0.001).